Photocatalytic Reduction of CO2 by Metal‐Free‐Based Materials: Recent Advances and Future Perspective. Issue 8 (28th February 2020) - Shen, Huidong; Peppel, Tim; Strunk, Jennifer; Sun, Zhenyu
Abstract : Photocatalytic CO2 reduction to produce valuable chemicals and fuels using solar energy provides an appealing route to alleviate global energy and environmental problems. Searching for photocatalysts with high activity and selectivity for CO2 conversion is the key to achieving this goal. Among the various proposed photocatalysts, metal‐free materials, such as graphene, nitrides, carbides, and conjugated organic polymers, have gained extensive research interest for photocatalytic CO2 reduction, due to their earth abundance, cost‐effectiveness, good electrical conductivity, and environmental friendliness. They exhibit prominent catalytic activity, impressive selectivity, and long durability for the conversion of CO2 to solar fuels. Herein, the recent progress on metal‐free photocatalysis of CO2 reduction is systematically reviewed. Opportunities and challenges on modification of nonmetallic catalysts to enhance CO2 transformation are presented. Theoretical calculations on possible reduction mechanisms and pathways as well as the potential in situ and operando techniques for mechanistic understanding are also summarized and discussed. Based on the aforementioned discussions, suitable future research directions and perspectives for the design and development of potential nonmetallic photocatalysts for efficient CO2 reduction are provided. Abstract : A comprehensive and up‐to‐date review on metal‐free photocatalysis of CO2 reduction is provided, highlighting surface modification of photocatalysts to enhance CO2 absorption and activation. Theoretical calculations and operando techniques are also summarized and discussed to gain insight into possible reduction mechanisms and pathways. Furthermore, future prospects and challenges in photocatalytic CO2 reduction by nonmetallic catalysts are envisioned.